Ipsilateral Testicular Catch-Up Growth Rate Following Microsurgical Inguinal Adolescent Varicocelectomy - Orhun Sinanoglu; Seyit Erkan Eyyupoglu; Sinan Ekici (The Scientific World Journal)
Objective. To evaluate the ipsilateral catch-up growth rates compared to contralateral testicular growth in adolescents with varicocele undergoing microsurgical inguinal varicocelectomy. Materials and Methods. Between December 2005 and May 2007, 39 adolescent patients with grade 2-3 varicocele admitted to our clinic with complaints of pain and/or testicular asymmetry were operated. Preoperative mean age was 14.5 ± 1.96 (9–17). Testicular volumes were assessed with ultrasound every 3 months. The available followup was 39 months. Results. In our series, mean testicular preoperative volumes were 9.07±3.19 mL for the right and 5.90±1.74 mL for the left. Mean testicular volumes at the end of follow up were 13.97±3.42 mL for the right and 12.20±4.05 mL for the left. The testicular catch-up growth approximately begins after the 9th month and significant catch-up occurred in the 12–24 months (P<0.05). Conclusion. Since testicular volume is the primary method of assessing testicular function in adolescents, testicular size can predict future fertility status significantly 9 months after surgical varicocele correction.